Effect on NOx Abatement Performance of Metallic and Bimetallic (Copper and Platinum) Photodeposition onto TiO2 Anatase - Ichsan, Chairul; Febriani, Widya (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
To enhance the TiO2 anatase's ability to degrade nitrogen oxides (NOx), this study seeks to optimize the photocatalytic activity, selectivity, and DeNOx index of anatase TiO2 nanoparticles through surface modification using metallic and bimetallic (Cu dan Pt) photodeposition. The samples' photocatalytic performance is assessed by NOx abatement measurement, while their characteristics are analyzed using UV-Vis diffuse reflectance and an X-ray diffractometer. According to the measurement, S6 (0.05% Pt/TiO2) has a photonic efficiency of 0.17 for the degradation of NOx, which is 2.15 times higher than bare TiO2. The DeNOx index, which combines selectivity and photonic efficiency, suggests that S9 (0.05% Pt + 0.1% Cu/TiO2) is the most effective sample in the visible light region, with a value of 0.01. Under broadband illumination, S6 has a DeNOx index of 0.13, which is the highest among all samples, while S9 has a moderate-level DeNOx index of 0.019. All samples have a higher DeNOx index than the bare anatase TiO2 nanoparticles. Bimetallic samples exhibit the best performance under visible light, whereas Pt-modified TiO2 anatase performs best in the broadband light range.